A bio-based flame retardant coating for improving flame retardancy and anti-dripping performance of polyamide 6 fabric. (September 2022) - Jin, Wen-Jie; Cheng, Xian-Wei; He, Wei-Lin; Gu, Liang; Guan, Jin-Ping
Highlights: Phytic acid and taurine are derived from different crops. Phytate taurine salt (PTS) is successfully synthesized by ion reaction. PTS coating displays high flame retardant efficiency and anti-dripping ability on PA6 fabric. PTS coating mainly works in condense- and gas-phase. PTS coating offers an effective and cleaner strategy to minimize fire hazards of PA6 textiles. Abstract: Eco-friendly and sustainable flame retardant (FR) approaches derived from natural products for polyamide 6 (PA6) fabrics are of interest. Therefore, a novel biomass phytate taurine salt (PTS) was synthesized using phytic acid and taurine, and then it was coated onto PA6 fabric. The chemical structure of PTS, and the flame retardant performance and mechanism, the washing durability and physical properties of coated PA6 fabrics were explored. The damaged length of coated PA6 fabrics reduced to 12.0 cm without droplets during the vertical burning test, achieving a UL94 V-0 level. The LOI increased from 23.0% to 31.8% after PTS coating. The results of cone calorimetry showed that the pHRR of PA6-PTS sample decreased by about 11.0% with a char residue of 12.0%. The investigations on violates and char residues confirmed that PTS coating improved the flame retardancy of PA6 fabric through a combined gas-phase and condensed-phase action. In addition, the coated PA6 fabrics could still maintain V-0 level after 15 washing cycles. The tensile strength of PA6 fabrics was also slightly improved after PTS coating. In general, this work developed a durable and sustainable PTS coating with excellent flame retardancy for PA6 fabric. Graphical abstract: Image, graphical abstract